Media-Related Out-of-School Contact with English in Germany and Switzerland Frequency, Forms and the Effect on Language Learning - Krüger, Maleika (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2023)
This open access book aimes to close a critical research gap in understanding how frequently German-speaking adolescents come into contact with the English language through various media channels, such as television, books, or the internet, and how this contact influences learners' English competences. In addition, this research project explores the effect of family background and gender on this contact. The analysis shows frequent contact with English-language media content by young learners in Germany and Switzerland. More frequent contact was associated with higher language competences. Differences could be found in the preferences of media content and type of media channels due to socio-economic family background and gender. About the author Maleika Krüger holds a Bachelor's degree in Sociology from the University of Göttingen and a Master's degree in Sociology and Social Research from the University of Cologne. She also minored in Occupational, Economic, and Social Psychology at both universities. She worked and taught as a research associate and lecturer in the field of sociology and educational science at the University of Applied Science and Arts in Northwestern Switzerland and the University of Potsdam. In 2021, she earned her doctoral degree from the Institute of Educational Science at the University of Basel.